Dampak Pandemi Covid-19 dalam Bidang Pendidikan di Kota Mataram - Wawan Samudera (Indonesian Publication Center, 2020)
Corona virus (Covid-19), which is a new type that is transmitted to humans, attacks disorders of the respiratory system, leading to death. Apart from these health problems, an issue that is no less important is the issue of education. Problems in the world of education due to the dismissal of educational institutions. This research was conducted using qualitative research. The results of the study concluded that with regard to children's education, it is very clear from the results of this study that the Covid-19 pandemic has an impact on the education sector in Mataram City.